Departmental h-Index: Evidence for Publishing Less?. Issue 1 (February 2017) - Tyrrell, Pascal N.; Moody, Alan R.; Moody, J. Oscar C.; Ghiam, Neda
Purpose: The h-index is an established method for determining an individual faculty member's impact on the scientific literature. The purpose of this study was to measure and describe over time the combined h-index of a large university medical imaging department. Materials and Methods: All faculty members from the Department of Medical Imaging, University of Toronto, were identified from administrative records for 6 separate years between 2000-2014. Individual members' and the departmental h-index were calculated using citation data from the Scopus database. Descriptive univariate statistics were reported. Factors contributing to the change in departmental h-index over time were assessed using linear regression analysis. Results: The number of faculty members increased from 117 in 2000 to 186 in 2014. The departmental h-index increased from 48 in 2000 to 142 in 2014. During this time period, the median h-index for faculty members increased from 4 (interquartile range 2-8) to 10 (interquartile range 5-19). Regression analysis revealed that for every additional staff member, the departmental h-index increased by 1.4 (standard error = 0.1, P < .01), whereas, by increasing the median h-index of members by 1 the departmental h-index increased by 15.7 (standard error = 0.6, P < . 01). Conclusion: Our study suggests that to increase a department's h-index, it is important to foster impactful research from within the faculty ranks of the department. The h-index of academic radiology departments is a meaningful tool that allows for evaluation from within and against other academic centres.